Airport capacity extension, fleet investment, and optimal aircraft scheduling in a multilevel market model: quantifying the costs of imperfect markets - Stefano Coniglio; Mathias Sirvent; Martin Weibelzahl (OR Spectrum, 2021)
We present a market model of a liberalized aviation market with independent decision makers. The model consists of a hierarchical, trilevel optimization problem where perfectly competitive budget-constrained airports decide (in the first level) on optimal runway capacity extensions and airport charges by anticipating long-term fleet investment and medium-term aircraft scheduling decisions taken by a set of imperfectly competitive airlines (in the second level). Both airports and airlines anticipate the short-term outcome of a perfectly competitive ticket market (in the third level). We compare our trilevel model to an integrated single-level (benchmark) model in which investments, scheduling, and market-clearing decisions are simultaneously taken by a welfare-maximizing social planner. Using a simple six airports example from the literature, we illustrate the inefficiency of long-run investments in both runway capacity and aircraft fleet which may be observed in aviation markets with imperfectly competitive airlines.
Keywords: 650; OR in airlines; Mixed-integer optimization; Multilevel optimization; Market design; Long-run investments